Why writing a new constitution after conflict can contribute to peace - Charlotte Fiedler (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
In every fourth post-conflict country a new constitution is written, but the effect of these post-conflict constitution-making processes on peace remains understudied. Constitution-making has become a corner stone of peacebuilding efforts in post-conflict societies and is widely supported by international actors. It is often seen as a main component of a political transition necessary in states that have experienced internal warfare. This is because a successful constitution-making process establishes a new and potentially permanent governance framework that regulates access to power. However, systematic analyses of the effect of post-conflict constitution-making on peace have been lacking. This Briefing Paper presents new, empirical evidence showing that post-conflict constitution-making can contribute to peace. Countries emerging from conflict often adopt new constitutions in order to signal a clear break with the past regime and to reform the institutions that are often seen as at least partially responsible for conflict having erupted in the first place. Post-conflict constitution-making has taken place in highly diverse settings – ranging from the aftermath of civil war, as in Nepal or South Africa, to interethnic clashes or electoral violence, as in Kyrgyzstan or Kenya. And in the current peace talks around Syria the question of writing a new constitution also plays a prominent role. Since academic evidence is lacking as to whether constitution-making can contribute to peace after civil war, it remains an open question whether efforts in this regard should be pursued by international actors. This Briefing Paper presents evidence that writing a new constitution positively influences post-conflict countries' prospects for peace (for the full analysis see Fiedler, 2019). It summarises innovative, statistical research on post-conflict constitution-making, conducted by the DIE project “Supporting Sustainable Peace”. Based on an analysis of 236 post-conflict episodes between 1946 and 2010, two main results with clear policy implications emerge: Writing a new constitution reduces the risk of conflict recurrence. The analysis shows a statistically significant and robust association between writing a new constitution after experiencing violent conflict and sustaining peace. International efforts to support post-conflict constitution-making are hence well-founded. The theoretical argument behind the relationship suggests that it is important that constitution-making processes enable an extensive inter-elite dialogue that helps build trust in the post-conflict period. Post-conflict constitution-making processes that take longer are more beneficial for peace. This is likely because the trust-building effect of constitution-making only occurs when enough time enables bargaining and the development of a broad compromise. International actors frequently pressure post-conflict countries to go through these processes very quickly, in only a matter of months. The results question this approach, as very short constitution-making processes do not positively affect peace.
Keywords: 330; Governance; Sicherheit; Frieden und fragile Staaten; Soziale Kohäsion